(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
An organized cervical cancer screening programme on a national level in Bangladesh can reduce mortality from cervical cancer. The Papannicolaou (PAP) smear is a highly effective screening test for the detection of cervical neoplastic changes. The success of the test has resulted in unrealistic expectations of the accuracy of the test by both referring medical practitioners and the public. This study is a comparison between interpretation based on cytopathological and histopathological tests and was undertaken to estimate the accuracy rate of the papanicolaou (PAP) test done among 2300 patients in two tertiary private medical college and hospital in the cytopathology and histopathology department during the period from June 2010 to July 2011 and women who have undergone for pap smear cytology test along with biopsy were selected. Detail history with clinical examination was performed and the findings were correlated. The reporting of PAP smears is done according to Bethesda 2001 classification and the CIN (cervical intraepithelial neoplasia) grading is used for histopathology reporting. The overall accuracy rate of the test was 90% (4 false negatives out of 40 positively selected patients). Considering the histopathology reports as the gold standard, PAP smear test is also found to be equally sensitive. But it is advised to perform biopsy (diagnostic test) if any abnormalities are detected in PAP smear cytology(screening test). J. Dhaka National Med. Coll. Hos. 2013; 19 (01): 49-53